2019
DOI: 10.1002/tox.22694
|View full text |Cite
|
Sign up to set email alerts
|

Reduced camptothecin sensitivity of estrogen receptor‐positive human breast cancer cells following exposure to di(2‐ethylhexyl)phthalate (DEHP) is associated with DNA methylation changes

Abstract: Di(2-ethylhexyl)phthalate (DEHP) has been considered as an estrogen receptor alpha (ERα) agonist due to its ability to interact with ERα and promote the cell proliferation of ERαpositive breast cancer cells. The impact of DEHP on the chemical therapy in breast cancer is little known. Two breast cancer cell lines, MCF-7 (ERα-dependent) and MDA-MB-231 (ERα-independent) were examined. We found that DEHP impaired the effectiveness of camptothecin (CPT) and alleviated the CPT-induced formation of reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…DEHP exposure was found to enhance cell proliferation through Wnt/βcatenin signaling and to promote non-small cell lung carcinoma (NSCLC) [45]. Our previous study showed that short-term and high-dose DEHP exposure (100 µM, 48 h) induced camptothecin (CPT) resistance in MCF7 cells through Wnt/β-catenin-associated epigenetic mutations; however, no effect was observed in MDA-MB-231 cells [46]. Phthalates (DEHP, BBP, and DBP) induce the proliferation of MCF7 cells through estrogenic activity, preventing apoptosis in the presence of 17β-estradiol [47], suggesting that DEHP has estrogenic activity; however, in our study, we found that long-term (>3 months) DEHP exposure had no effect on ER-positive MCF7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…DEHP exposure was found to enhance cell proliferation through Wnt/βcatenin signaling and to promote non-small cell lung carcinoma (NSCLC) [45]. Our previous study showed that short-term and high-dose DEHP exposure (100 µM, 48 h) induced camptothecin (CPT) resistance in MCF7 cells through Wnt/β-catenin-associated epigenetic mutations; however, no effect was observed in MDA-MB-231 cells [46]. Phthalates (DEHP, BBP, and DBP) induce the proliferation of MCF7 cells through estrogenic activity, preventing apoptosis in the presence of 17β-estradiol [47], suggesting that DEHP has estrogenic activity; however, in our study, we found that long-term (>3 months) DEHP exposure had no effect on ER-positive MCF7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Phthalates act as agonists for PPARs and activate the BARC gene through molecular signaling (Guyton et al, 2009;Rusyn and Corton, 2012;Sarath Josh et al, 2014). DEHP at high doses (100 and 500 µM) impaired the efficacy of camptothecin (CPT), an antitumor agent and reduced CPT-induced formation of reactive oxygen species (ROS) in ERα-positive MCF-7 cells (Chou et al, 2019). The impaired response of CPT in DEHP-exposed MCF-7 cells was mediated by epigenetic changes.…”
Section: Cancermentioning
confidence: 99%
“…The impaired response of CPT in DEHP-exposed MCF-7 cells was mediated by epigenetic changes. MCF-7 cells after 48 hrs of exposure to 100 µM DEHP displayed considerable changes in patterns of DNA methylation, including hypermethylation of 700 genes and hypomethylation of 221 genes (Chou et al, 2019). In a Danish nationwide cohort of 1.12 million women who were followed for 10 years, 84% of breast cancers were ER-positive, and high level DBP exposure (≥10,000 mg) was directly related with a 2-fold increase in the rate of estrogen receptor-positive breast cancer risk (Ahern et al, 2019).…”
Section: Cancermentioning
confidence: 99%
“…Di(2-ethylhexyl) phthalate (DEHP) (Figure 10b), estrogen receptor alpha (ERα) agonist due to its ability to interact with ERα and promote the cell proliferation of ERα-positive breast cancer cells, significantly protected MCF-7 cells against the genotoxicity of camptothecin [562]. Actinomycin D obtained from various Streptomyces strains decreases Mcl-1 expression in lung cancer cells [563], induces p53-independent cell death in leukemia [564], synergistically suppressed multiple metastasis of TRAIL-resistant colon cancer in the liver with soluble TRAIL gene [565]. Hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin and mitomycin C (Figure 10c) (obtained from Streptomyces caespitosus) is the only protocol to demonstrate an adjuvant HIPEC benefit in colorectal cancer patients at high risk for peritoneal failure and an alternative to highdose and short-term oxaliplatin [566].…”
Section: Mundulea Sericeamentioning
confidence: 99%